Teknik Bagging Pada Klasifikasi Agoritma C4.5 Untuk Menentukan Persetujuan Peminjaman di Koperasi - Daryanto, Daryanto; Rahman, Miftahur; Wardiyanto, Dedep Vicky (Universitas PGRI Kanjuruhan Malang, 2022)
Cooperatives are an economic organization that is different from other economic organizations, cooperatives consist of weak groups by making mutual agreements, and cooperation of members to achieve mutual welfare and each member is able to carry out his obligations as a cooperative member organization. In this study, the bootstrap aggregating technique in 17 tests with 2-fold, 5-fold, and 10-fold divisors obtained the highest accuracy results, namely 56.92% for 2-fold, 65.38% for 5-fold, and 76. 92% at 10-fold.